Salivary Thiocyanate Levels and Buccal Mucosal Cells Changes in E-cigarette Users and Traditional Smokers - Mufeed Muhammad Jawad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Background: The rising use of electronic cigarettes (e-cigarettes) has become a significant public health issue. While e-cigarettes are seen as a safer alternative to traditional smoking, they may still expose users to toxic chemicals that could adversely affect oral health. This study aims to investigate the cytomorphometric changes in buccal mucosal cells among different smoking groups, including e-cigarette vapers, traditional smokers of varying intensities, and non-smokers, and to correlate these findings with salivary thiocyanate levels, a biomarker for cyanide exposure.